What are older people and their families looking for in an aged care services provider?. (6th November 2019) - Parkinson, Lynne; Banbury, Annie; Hillman, Wendy; Lee, Julie
Abstract: Objective: Choosing an aged care services provider is a complex decision. This study explored the factors older people and their families consider during this decision‐making process. Methods: Four focus groups (two in rural, two in urban Queensland) included older people using and not using aged care services and family members seeking residential aged care services. Results: Four themes emerged from the analysis of participants' perspectives, with human needs (such as autonomy, caring, respect, certainty) and organisational values (such as person‐centredness) viewed as most important. Costs, value for money and regulatory considerations were sometimes perceived to be more important than locality. The perceived significance of facilities, services and amenity needs differed according to age and time of life, although a clear pathway to residential aged care facilities from living in the community was desired. Finding information, planning and choosing providers was seen to be hindered by lack of accessible, quality information. Conclusions: Meeting human needs (such as autonomy, caring, respect, certainty) through organisational values (such as person‐centredness) is the most desirable factor according to the perceptions of older people and their families when choosing an aged care services provider.